Study of Antioxidant Activity of Some Medicinal Plants Having High Content of Caffeic Acid Derivatives - Tajner-Czopek, Agnieszka (Antioxidants (Basel), 2020)
Recently, there has been increasing interest in medicinal plants, due to their content of health-promoting compounds, e.g., caffeic acids derivatives. Hence, the aim of this work was to study the antioxidant activity of extracts obtained from the following medicinal plants: caraway (Carum carvi L.), coltsfoot (Tussilago farfara L.), dandelion (Taraxacum officinale F.H.Wigg.), lovage (Levisticum officinale L.), tarragon (Artemisia dracunculus L.) and white mulberry (Morus alba L.), characterized by their high content of caffeic acid derivatives. The water-ethanolic extracts were characterized on average by about 9 times higher contents of caffeic acid derivatives level than water extracts. Both in water and water-ethanolic extracts, the dominant phenolic acid was 5-CQA (5-O-caffeoylquinic acid) and 3,4-diCQA (3,4-dicaffeoylquinic acid), then CCA-1 (chicoric acid isomer 1), which appeared only in water-ethanolic extracts. Extracts from dandelion contained compounds such as CTA (caftaric acid), CCA-1 (chicoric acid isomer 1) and CCA-2 (chicoric acid isomer 2), which were not detected in other plant extracts examined in this work. The water-ethanolic extracts from coltsfoot and tarragon were characterized by a high content of di-caffeoylquinic acids, especially 3,4-diCQA and 3,5-diCQA, respectively. It has been stated that there is a positive correlation between caffeic acid derivatives and antioxidant activity (radical cation scavenging activity (ABTS) and radical scavenging activity (DPPH)), especially in water-ethanolic extract of medicinal plants.